1978
DOI: 10.1093/geronj/33.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on the Peripheral Blood Lymphocyte Count

Abstract: Analysis of 1684 inpatient and 884 outpatient peripheral blood counts revealed the following: (1) The absolute lymphocyte count declines sharply from 5000/microletre to 2000/microletre in the first two decades, remains constant for three decades, then declines at an accelerated rate beginning in the 40s, to reach 1500/microletre at age 90. (2) The absolute granulocyte count does not show age-dependent variation, remaining essentially constant throughout life. (3) The values of absolute lymphocytes are indistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
2
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 0 publications
4
19
2
1
Order By: Relevance
“…7A). Indeed, consistent with data from humans, this phenomenon was clearly attributed to older macaques having significantly lower lymphocyte counts in peripheral blood than younger animals (data not shown) (16). Therefore, we compared the frequency of CD4 ϩ T cells in each group of animals (Fig.…”
Section: Low Level Of Infection Among Dn T Cells In Mangabeyssupporting
confidence: 82%
“…7A). Indeed, consistent with data from humans, this phenomenon was clearly attributed to older macaques having significantly lower lymphocyte counts in peripheral blood than younger animals (data not shown) (16). Therefore, we compared the frequency of CD4 ϩ T cells in each group of animals (Fig.…”
Section: Low Level Of Infection Among Dn T Cells In Mangabeyssupporting
confidence: 82%
“…Between the second and seventh decade a moderate decline in lymphocytes [39] and erythrocytes [40] has been described. When we analyzed DNAm of the three relevant CpG sites (cg02228185 in ASPA , cg25809905 in ITGA2B , and cg17861230 in PDE4C ) in a publicly available dataset of cell type-specific DNAm profiles [41] the results indicated that the age predictions made using our epigenetic aging signature were not evoked by myeloid skewing (Figure S9a in Additional file 1).…”
Section: Resultsmentioning
confidence: 99%
“…The parameters were similar to those identified in a previous study (29), which demonstrated that total white blood cell and lymphocyte counts decrease with age, while neutrophil, monocyte and eosinophil counts increase in mice. However, in humans, lymphocyte counts are significantly decreased in the first two decades and remain constant for the following three decades, and demonstrate a more prominent decrease thereafter (30).…”
Section: Discussionmentioning
confidence: 99%